Glimpse into the design of MRS instrument. Issue 2 (1st January 2014) - Legchenko, A.; Pierrat, G.
ABSTRACT: The Magnetic Resonance Sounding method (MRS) was developed in the former USSR in the late 1970s. Nowadays, available MRS instruments are more compact and reliable, and enormous progress has been made in electronics, computers and materials. Therefore, we can hope that it may be possible to increase the maximum depth of water detection and to improve the resolution of the method by using a larger current in the loop. Quite naturally, the questions arise: what are the practical limits of the MRS method and how much should be transmitting power to get the maximum depth of investigation? In this paper, we analyse the depth of groundwater detection and the vertical resolution of the MRS assuming different loops and different power levels of the current generator. The originality of our approach consists of a joint analysis of the maximum depth of investigation using accept able loop voltage and the modifications in the instrument design necessary for the improvements. We show that even under very favourable conditions it would be difficult to get significant improvement in the depth of investigation using currently available instruments. For example, under favourable noise conditions when rocks have low electrical conductivity and are non‐magnetic, a 20 m thick water saturated sand layer can be detected at a depth of about 325 m using an existing instrument (4 kV of the loop voltage) with a 400 × 400 m 2 square loop. A 20% increase in the detection depth (390 m instead of 325 m) requires more powerful electronic equipment (16 kV instead of 4 kV) thus rendering the MRS system larger and heavier. However, using a 16 kV instrument allows us to increase the resolution depth by about 80% (from 120 m to 215 m). When rocks are electrically conductive, the screening of the MRS signal limits the depth of investigation and allows for only minor improvements even with a much more powerful current generator.